TANTANGAN IMPLEMENTASI MODEL PEMBELAJARAN BLANDED LEARNING DI SMP NEGERI 1 DAYUN MASA PANDEMIK COVID-19 - Asril, Asril; Nainggolan, Tiur Malina; Kurniawan, Robi Dwi; Sawitri, Isma; Muktianis, Nita (Jurnal Manajemen Pendidikan, 2020)
Education is one of the leading factors in advancing a nation. The implementation of education in the midst of the COVID-19 pandemic, has been running with innovations from the government on the learning model applied in schools. We know this model as a bold, captivating and combined learning system. In connection with the above explanation, we will try to identify what challenges will be faced by SMPN 1 Dayun in implementing the Blended Learning model during the covid-19 pandemic. This study uses a descriptive qualitative method, where in obtaining information and data we use survey techniques, observations, and interviews with the school. The subjects in this study were all 7th grade students of SMP Negeri 1 Dayun for the 2020/2021 academic year. The results showed that SMPN 1 Dayun was considered successful in implementing the Learning Method even though it had to face various obstacles and obstacles in its implementation